Contracting with Imperfect Commitment and Noisy Communication - Helmut Bester; Roland Strausz (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2003)
Lecture on the first SFB/TR 15 meeting, Gummersbach, July, 18 - 20, 2004: This paper provides an analytical framework for studying principal-agent problems with adverse selection and limited commitment. By allowing the principal to use noisy communication we solve two fundamental problems of contracting with imperfect commitment: First, we identify the relevant incentive constraints by showing that only 'local' constraints are binding if the agent's preferences satisfy a single-crossing property. Second, we show that one can restrict the dimensionality of the message spaces of the communication device to the number of the agent's types. As we illustrate in an example, these findings allow us to derive the optimal contract by a similar procedure as in contracting problems with full commitment.
urn:nbn:de:bvb:19-epub-13544-0
Keywords: D82; C72; 330; contract theory; communication; imperfect commitment; adverse selection